2012
DOI: 10.1186/1472-6947-12-98
|View full text |Cite
|
Sign up to set email alerts
|

Supporting meningitis diagnosis amongst infants and children through the use of fuzzy cognitive mapping

Abstract: BackgroundMeningitis is characterized by an inflammation of the meninges, or the membranes surrounding the brain and spinal cord. Early diagnosis and treatment is crucial for a positive outcome, yet identifying meningitis is a complex process involving an array of signs and symptoms and multiple causal factors which require novel solutions to support clinical decision-making. In this work, we explore the potential of fuzzy cognitive map to assist in the modeling of meningitis, as a support tool for physicians … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 51 publications
(40 reference statements)
0
19
0
2
Order By: Relevance
“…•The degree of impact was then converted from its qualitative value (M, H, VH) to its quantitative value of 0.648 using FL concepts as described in [87]. All three studies indicated that as levels of addiction increase they exert a positive effect resulting in increases in levels of homelessness.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…•The degree of impact was then converted from its qualitative value (M, H, VH) to its quantitative value of 0.648 using FL concepts as described in [87]. All three studies indicated that as levels of addiction increase they exert a positive effect resulting in increases in levels of homelessness.…”
Section: Methodsmentioning
confidence: 99%
“…For each edge, we constructed an individual FIS and the defuzzified value, in this case 0.5, is assigned to the edge. More information about the procedure can be found in [87-90]. …”
Section: Methodsmentioning
confidence: 99%
“…In another study, FCM has been used to predict the autistic behavior [23,24]. Another FCM tool has been used to diagnose meningitis and based on the severity of the disease, decisions regarding the most appropriate treatment were recommended [25]. In dental implantation the patient's anatomical and other conditions were analyzed and FCM was used as a decision making tool to determine the type of abutment from more than 370 items [26].…”
Section: Literature Surveymentioning
confidence: 99%
“…FCM was also used by the Mago et al research to develop the required knowledge-based structure used for recognizing the specific causes and the symptoms of meningitis disease in children. This system can be implemented as a dependable instrument in supporting the physician's to better their decision making processes [39].…”
Section: The Fuzzy Cognitive Map Techniquementioning
confidence: 99%